Research on Data Integration of the Semantic Web Based on Ontology Learning Technology - Hongsheng Xu; Ruiling Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Goal of ontology learning is to use machine learning and statistical techniques, by means of automatic or semi-automatic, and obtain the expected from the existing data resources. Web data integration based on ontology is web data mapping information in the source to the process of ontology concepts. The goal of semantic Web is to provide a computer for semantic Internet information can be understood, thus the computer to identify the information, and the automatic interpretation, exchange and processing. The paper presents the research on data integration of the semantic web based on ontology learning technology. Theory and experiments show that compared with the method of concept lattice construction algorithm has certain superiority. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3889